Post Herpetic Anti-NMDA- Receptor Encephalitis in an 18-month-old Infant - Eslamiyeh, Hossein; Ranjbar Jamalabadi, Reihane; Askarbioki, Mohsen (Iranian Journal of Child Neurology, 2023)
Herpes simplex encephalitis (HSE), caused by herpes simplex virus type 1 (HSV-1), is the most common cause of severe sporadic encephalitis worldwide. HSE is occasionally accompanied by the recurrence of clinical symptoms that usually occur a few weeks following the initial infection. According to recent studies, the recurrence can be due to a secondary autoimmune mechanism rather than the virus invasion. One of the most common etiologies for autoimmunity is Anti-NMethyl D-Aspartate receptor encephalitis. This disorder is a treatable autoimmune encephalitis manifesting as movement disorder or neuropsychological involvement